A study on the spatial organization and structural evolution of Suzhou historical districts from a multiscale perspective: conflict and integration between tradition and modernity - Zehao Zhang; Yinying Tao; Kai Zhou (Journal of Asian Architecture and Building Engineering)
As a vital element of the built heritage of East Asia, historical districts in the region encapsulate the collective memory of urban development, reflecting the distinctive urban fabrics and cultural characteristics of the area. However, with the rapid socioeconomic progress in East Asia, traditional historical districts are facing an increasing number of challenges associated with renewal and transformation. This study aims to evaluate the spatial organisation and structural evolution of Suzhou historical districts from a multiscale perspective, with a focus on understanding the conflict and integration between traditional core areas and modern redevelopment zones. Specifically, the study examines the influence of spatial configuration on pedestrian movement by analysing spatial variables such as integration, choice, total depth, synergy, and intelligibility. To address these challenges, the paper proposes a research approach grounded in space syntax to provide a comprehensive analysis and description of the district’s spatial organisation. The findings reveal the characteristics of spatial organisation and structure across various scales, emphasising the importance of spatial logicality and consistency. Moreover, the paper provides recommendations for optimising spatial organisation and structure and practical strategies for reconciling the relationship between traditional core areas and modern redevelopment zones.